FTO attenuates TNF-α-induced damage of proximal tubular epithelial cells in acute pancreatitis-induced acute kidney injury via targeting AQP3 in an N6-methyladenosine-dependent manner - Xinghui Li; Qi Liang; Lu Liu; Shujun Chen; Yong Li; Yu Pu (Renal Failure)
Background Acute kidney injury (AKI) is a frequent complication of severe acute pancreatitis (SAP). Previous investigations have revealed the involvement of FTO alpha-ketoglutarate-dependent dioxygenase (FTO) and aquaporin 3 (AQP3) in AKI. Therefore, the aim of this study is to explore the association of FTO and AQP3 on proximal tubular epithelial cell damage in SAP-induced AKI.Methods An in-vitro AKI model was established in human proximal tubular epithelial cells (PTECs) HK-2 via tumor necrosis factor-α (TNF-α) induction (20 ng/mL), after which FTO and AQP3 expression was manipulated and quantified by quantitative real-time PCR and Western blotting. The viability and apoptosis of PTECs under various conditions, and reactive oxygen species (ROS), superoxide dismutase (SOD), and malonaldehyde (MDA) levels within these cells were measured using commercial assay kits and flow cytometry. Methylated RNA immunoprecipitation and mRNA stability assays were performed to elucidate the mechanism of FTO-mediated N6-methyladenosine (m6A) modification. Western blotting was performed to quantify β-catenin protein levels in the PTECs.Results FTO overexpression attenuated the TNF-α-induced decrease in viability and SOD levels, elevated apoptosis, increased levels of ROS and MDA, and diminished TNF-α-induced AQP3 expression and reduced β-catenin expression, but its silencing led to contradictory results. FTO negatively modulates AQP3 levels in RTECs in an m6A-depednent manner and compromises AQP3 stability. In addition, all FTO overexpression-induced effects in TNF-α-induced PTECs were neutralized following AQP3 upregulation.Conclusion FTO alleviates TNF-α-induced damage to PTECs in vitro by targeting AQP3 in an m6A-dependent manner.